2003
DOI: 10.1007/s00059-003-2439-2
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Diagnosis of the Fetus with Hypoplastic Left Heart Syndrome

Abstract: The low percentage of intention to treat among patients in our center (34%) is in accordance with the percentage found in another study from the UK (36.2%), but differs significantly from reported series across the Atlantic (67%). Prenatal diagnosis of the HLHS provides opportunities not only for getting patients in optimal preoperative condition when surgery is offered, but also for in-depth counseling of the parents on this severe malformation. A minority of parents faced with the difficult decision of possi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 30 publications
(44 reference statements)
2
13
0
1
Order By: Relevance
“…In other countries a large percentage of parents chose termination specifically for HLHS. For example, the percentage of parents who chose termination was 44% 6 and 60% 7 in Britain, 18% 8 and 45% 9 in USA, 50% 10 in the Netherlands and 71% 11 in France. Not unexpectedly, the incidence of termination for HLHS increases as the diagnosis is made more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…In other countries a large percentage of parents chose termination specifically for HLHS. For example, the percentage of parents who chose termination was 44% 6 and 60% 7 in Britain, 18% 8 and 45% 9 in USA, 50% 10 in the Netherlands and 71% 11 in France. Not unexpectedly, the incidence of termination for HLHS increases as the diagnosis is made more frequently.…”
Section: Discussionmentioning
confidence: 99%
“…29,31 Based on population data from the Baltimore-Washington infant study (BWIS) Boughman et al 32 found that 13.5% (5/38) of first degree relatives of children with HLH had symptomatic congenital heart disease themselves. 32,33,34,35 One interpretation of these figures is that a significant percentage of cases of HLH have a genetic aetiology. The "precurrence risk" -the risk to relatives born before the study infant of a heart defect -was therefore 13.5% in this study.…”
Section: Recurrence Riskmentioning
confidence: 99%
“…What is a tolerable risk for one mother to improve the chance of a more normal life for her unborn fetus may differ vastly from that for another mother of a different culture, socioeconomic class, religious background, or personal family situation. 7 Safeguards must be in place to ensure that parents are counseled by more than 1 individual about the current state of knowledge and possible alternatives to fetal catheter intervention, including termination of pregnancy (in some cases), continuing the pregnancy without intervention (and then choosing among options such as palliative care, Norwood operation, or transplantation), and possible fetal intervention. New programs should be overseen by an institutional review board or innovative practice committee.…”
mentioning
confidence: 99%